Pengaruh Metode Follow The Line (Ftl) Terhadap Hasil Belajar Siswa Mata Pelajaran Al-Qur’an Hadist Kelas I Madrasah Ibtidaiyah 02 Pondok Modern Muhammadiyah Paciran Lamongan Tahun Pelajaran 2023/2024 - Silvia, Nayla Fadiatus; Husniyah, Himmatul (Jurnal Pendidikan Bahasa Arab, 2024)
This research discusses the influence of the Follow The Line (FTL) learning method on student learning outcomes in Al-Qur'an Hadith subjects Class I Madrasah Ibtidaiyah Muhammadiyah 02 Pondok Modern Paciran for the 2023/2024 academic year. Against the background of students who lack interest in learning to read and write the Al-Qur'an, there are still students who are less accustomed to reading and writing the Al-Qur'an and have different student backgrounds, as well as teachers who still use conventional learning or teachers who dominate the learning process, especially in Al-Qur'an Hadith subjects. To address this problem, researchers are interested in using the Follow The Line (FTL) Learning Method as the main model in the Al-Qur'an Hadith learning process. The formulation of the problem behind the research is "Is there an influence of the Follow The Line (FTL) learning method on improving student learning outcomes in Al-Qur'an and Hadith subjects in class I Madrasah Ibtidaiyah Muhammadiyah 02 PaciranLamongan for the 2023/2024 academic year?". This research uses a quantitative type of research. Using the Pre-Experiment design method with the one group pretest-posttest design technique. Data collection techniques were in the form of observations and tests with a sample of 38 students from class I of Madrasah Ibtidaiyah Muhammadiyah 02 Pondok Modern Paciran. The test used the Pearson Product Moment correlation which obtained a calculated r of 0.740, the number of respondents was 38 with dk – 2 = 36 which obtained an r table of 0.320 at a significance level of 5%. So rcount>rtable (0.740> 0.320). This shows that H0 is rejected and H1 is accepted with the interpretation of the correlation coefficient assessment which was found to be 0.740, which is between 0.60 - 0.799 which is included in the strong category. Meanwhile, for significance testing using the t test, the results were tcount 6.607 and ttable 2.028 so it can be concluded that tcount>ttable which means that H0 is rejected and H1 is accepted. Thus, it can be concluded that there is a strong and significant influence of the Follow The Line (FTL) learning method on student learning outcomes in the Al-Qur'an and Hadith subjects class I Madrasah Ibtidaiyah Muhammadiyah 02 Pondok Modern Paciran for the 2023/2024 academic year.